[1,2,4]triazino[2,3-c] quinazoline hybrids with azole and azine heterocycles: design, synthesis, antibacterial and antiradical activity - Grytsak, O. A.; Schabelnyk, K. P.; Kinichenko, A.; Komarovska-Porokhnyvets, O.; Lubеnets, V.; Voskoboinik, O.; Kovalenko, S.; Грицак, О. А.; Шабельник, Костянтин Петрович; Кініченко, Анна Олександрівна (My University, 2024)
The aim. Present paper devoted to the purposeful search of a promising biologically active compounds among heterocyclic hybrids combining in their structure [1,2,4]triazino[2,3-c]quinazoline system and a “pharmacophoric” azole or azine fragment, joined through an alkylthio linker group. Material and methods. Methods of synthetic organic chemistry were used to prepare target compounds. The purity and structure of the synthesized compounds were confirmed by elemental analysis, HPLC-MS, and ¹H NMR spectrometry. Radical-scavenging activity was estimated using DPPH-assay, antimicrobial activity was studied by serial dilution method. Results. A combinatorial library of 30 novel heterocyclic hybrids was designed and synthesized. The target compounds were obtained via the interaction of 6-chloroalkyl-3-R-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones and corresponding heterocyclic thiones in the presence of a base. The synthesized compounds were studied for their radical scavenging and antimicrobial activity. Most of the obtained compounds revealed low antimicrobial activity against studied strains. However, the heterocyclic hybrid combining triazinoquinazoline, thiadiazole, and 4-fluorophenyl moieties (compound 2.14) inhibited the growth of S. aureus, E. coli, and M. luteum. Among the obtained compounds, five heterocyclic hybrids demonstrated significant DPPH radical scavenging activity (30.41–43.53 %). The “structure-activity” correlations were evaluated and discussed. It was estimated that “linker” alkylthio-group modification resulted in the most pronounced changes in the radical scavenging activity of obtained compounds. Conclusions. Triazinoquinazoline-based heterocyclic hybrids are promising objects for further screening for antimicrobial activity and pharmacological effects associated with antiradical properties.
Keywords: heterocyclic hybrids; synthesis; radical scavenging activity; antimicrobial and antifungal activity; SAR-analysis